Food Crisis in Nepal (Nepalese Journal of Development and Rural Studies, 2022)
The food crisis is a global and local issue since the expansion of COVID-19 and after that period. Most developing countries including Nepal has been facing food deficit before and after the pandemic because of the irregular supply-demand chain of food and increasing food dependency on foreign countries.  According to WFP (2022), 345 million people in 85 countries have been facing food crises in the world in 2022 and most of them are from Africa, Asia, and Latin America. According to Pandey &Fusaro (2020), approximately 56% of women overall and 76% of Dalit women reported having food insecurity. Similarly, most of the districts of Karnali and some of the districts of Madhesh Pradesh and SudurPachhim Pradesh has been facing food deficit due to the low productivity and the bad policies of the government.